2014
DOI: 10.1108/et-06-2013-0074
|View full text |Cite
|
Sign up to set email alerts
|

Do real estate courses sufficiently develop graduates’ employability skills? Perspectives from multiple stakeholders

Abstract: Purpose – The purpose of this paper is to investigate whether Royal Institution of Chartered Surveyors (RICS) accredited real estate courses in the UK have equipped real estate graduates with sufficient relevant employability skills to embark on a career in the profession. This paper considers the perspectives of four stakeholders – employers, human resource managers, graduates and course directors of RICS-accredited real estate courses – in the UK. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 22 publications
6
35
0
4
Order By: Relevance
“…Scholars have attempted to classify competencies into two categories, 'hard' skills and 'soft' skills (Deaconu et al, 2014;Dunbar et al, 2016;Orr et al, 2011;Poon, 2014;Stewart et al, 2016). Hard skills are those connected with the technical aspects of acquiring the knowledge to perform a job (Matsouka and Mihail, 2016), and soft skills are those related to personal interaction and are behavioural in nature (Andrews and Higson, 2008).…”
Section: Literature Review Definitions and Categories Of Graduate Commentioning
confidence: 99%
See 3 more Smart Citations
“…Scholars have attempted to classify competencies into two categories, 'hard' skills and 'soft' skills (Deaconu et al, 2014;Dunbar et al, 2016;Orr et al, 2011;Poon, 2014;Stewart et al, 2016). Hard skills are those connected with the technical aspects of acquiring the knowledge to perform a job (Matsouka and Mihail, 2016), and soft skills are those related to personal interaction and are behavioural in nature (Andrews and Higson, 2008).…”
Section: Literature Review Definitions and Categories Of Graduate Commentioning
confidence: 99%
“…Researchers argue that soft skills are more important and are in higher demand by employers (Dunbar et al, 2016;Fleming et al, 2009;Orr et al, 2011;Poon, 2014;Stewart et al, 2016). However, in a qualitative study, Rainsbury et al (2002) found that hard skills and soft skills were perceived to be equally important by graduates and students.…”
Section: Employers' Views On Graduate Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of employability can be associated with the way companies function in modern times (Helyer & Lee, 2014). In order to design jobs today, individuals are in need to interact and work with teams to accomplish their organizational objectives (Matsouka & Mihail, 2016;Poon, 2014).…”
Section: A N N U a L D I S T R I B U T I O N O F A R T I C L E S -N =mentioning
confidence: 99%